1993
DOI: 10.1254/jjp.63.251
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Mediators and Mechanisms Are Involved in the Adaptive Cytoprotection Provided by Certain Mild Irritants

Abstract: ABSTRACT-We investigated the participation of prostaglandins (PG) and nitric oxide (NO) in adaptive cytoprotection using 0.6 N HCl-induced gastric lesions in the rat stomach. Indomethacin reversed the pro tective effect of 0.2 N HCl more strongly than that of 0.35 N HCI, both of which markedly inhibited HCI ulcer. lV°-Nitro-L-arginine (L-NNA) did not affect the protective effect afforded by either 0.2 N HCl or 0.35 N HCI. Combined pretreatment with indomethacin and L-NNA did not diminish the protective action … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…These observations would seem to imply that induction of this enzyme represents a mechanism of local intestinal damage. This being the case, one possible interpretation of the data reported by Tepperman and Soper (24) is that LPS causes mild irritation to the gastric mucosa through induction of iNOS and thereby elicits an adaptive cytoprotective response in the stomach (8,28). However, Ferraz et al (7) recently reported that endotoxin pretreatment enhanced the susceptibility of the stomach to damage and that this effect was negated by NOS inhibition with aminoguanidine, which is more selective for iNOS.…”
mentioning
confidence: 99%
“…These observations would seem to imply that induction of this enzyme represents a mechanism of local intestinal damage. This being the case, one possible interpretation of the data reported by Tepperman and Soper (24) is that LPS causes mild irritation to the gastric mucosa through induction of iNOS and thereby elicits an adaptive cytoprotective response in the stomach (8,28). However, Ferraz et al (7) recently reported that endotoxin pretreatment enhanced the susceptibility of the stomach to damage and that this effect was negated by NOS inhibition with aminoguanidine, which is more selective for iNOS.…”
mentioning
confidence: 99%
“…In addition to PG, the activation of the efferent function of capsaicin‐sensitive splanchnic afferents leading to a CGRP–NO‐dependent increase in gastroprotective vasodilatory mechanisms has been identified pharmacologically and biochemically. Medullary TRH is involved in the vagal‐dependent adaptive gastric protection induced by intragastric pretreatment with low acid or EtOH, as shown by the use of TRH antibody injected into the DVC and the similarity of peripheral transmitters mediating central TRH and adaptive gastric protection 75 . Other specific neuropeptides, such as PYY, somatostatin analogues and members of the CGRP family, also act centrally to protect gastric mucosa against EtOH injury through vagal pathways involving PG, CGRP, NO and/or VIP (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Medullary TRH is involved in the vagal-dependent adaptive gastric protection induced by intragastric pretreatment with low acid or EtOH, as shown by the use ofTRH antibody injected into the DVC and the similarity of peripheral transmitters mediating central TRH and adaptive gastric protection. 75 Other specific neuropeptides, such as PYY, somatostatin analogues and members of the CGRP family, also act centrally to protect gastric mucosa against EtOH injury through vagal pathways involving PG, CGRP, NO and/or VIP (Table 1).…”
Section: Discussionmentioning
confidence: 99%